Analisis Penentuan Tarif Jalan Tol Cibitung – Cilincing Menggunakan Metode Pendekatan Ability To Pay (ATP) dan Willingness To Pay (WTP) - Sepriyanna, Irma; Pranata, Roi (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2024)
Transportation infrastructure and networks play a very large role in serving the movement of human activities, goods and services. Therefore, it is necessary to have a transportation network with good conditions and service levels that can connect each other between regions quickly and easily. One solution to overcome this condition is to build toll roads to pass traffic safely, comfortably, smoothly and even economically. The Cibitung-Cilincing toll road section is part of the Jakarta Outer Ring Road II (JORR II) located in a North-South direction corridor, starting from the Cibitung Interchange on the Jakarta - Cikampek Toll Road KM 25, heading north in Babelan sub-district and continuing to West direction meets the North Outer Ring at the Cilincing interchange. This research was conducted as a reference and recommendation for the current Cibitung - Cilincing toll road tariff. The number of respondent samples used was 100 respondents in class 1 vehicles, and 120 respondents in class 2 vehicles. Data collection was carried out by distributing questionnaires and direct interviews related to the socio-economic characteristics and travel characteristics of the respondents. The tariff recommendation that will be obtained is by using the Ability to Pay (ATP) and Willingness to Pay (WTP) approaches. The results of the study can be seen the socio-economic characteristics and travel characteristics of toll road users. The average ATP value in group 1 was Rp. 2,233/Km and for group 2 is Rp. 2,408/Km. The average WTP value in group 1 is Rp. 1,863/Km and for group 2 is Rp. 2,775/Km